Improvement of Meloxicam Solubility Using a β-Cyclodextrin Complex Prepared via the Kneading Method and Incorporated into an Orally Disintegrating Tablet - Ahmad Ainurofiq; Syaiful Choiri; Muhamad Ali Azhari; Chaterin Romauli Siagian; Bambang Budi Suryadi; Fea Prihapsara; Sholichah Rohmani (Advanced Pharmaceutical Bulletin, 2016)
Purpose: The aim of this research was to formulate and develop an orally disintegrating tablet (ODT) that incorporated a MEL/β-CD complex, using a quality by design (QbD) approach to enhance solubility and drug release. Methods: Multiple regression linear analysis was conducted to develop the kneading process and ODT formulation. Mixing time and amount of solvent were used as independent variables in kneading process optimisation, while the superdisintegrants were used to obtain the desired formulation. Fourier transform infrared spectroscopy and differential scanning calorimetry were performed for complex characterization. Results: MEL/β-CD complexation was successful in enhancing MEL solubility. The results suggest that increasing the amount of solvent and mixing time enhances drug loading and drug release. However, increased solvent amounts present the problem of removing the solvent. Primojel and Polyplasdone had a significant effect on the water wicking and tablet disintegration process (p<0.05), although Polyplasdone negatively affected tablet hardness. Both an optimized KN process and ODT formulation were obtained using a QbD approach. Conclusion: Incorporation of the MEL/β-CD complex during ODT formulation using the QbD approach serves as a model for ODT product development, with optimal product performance based on the specification of quality target product profiles. To understand more specific phenomena, one point in the middle of the design for each factor should be added to more powerfully estimate this effect and avoid the lack of estimate due to an inadequate equation.